МАЙОРОВ А.В. ГАЛИЦКО-ВОЛЫНСКАЯ РУСЬ. ОЧЕРКИ СОЦИАЛЬНОПОЛИТИЧЕСКИХ ОТНОШЕНИЙ В ДОМОНГОЛЬСКИЙ ПЕРИОД. КНЯЗЬ, БОЯРЕ И ГОРОДСКАЯ ОБЩИНА. – СПБ.: УНИВЕРСИТЕТСКАЯ КНИГА, 2001. – 640 С (Zaporizhzhia Historical Review, 2021)
The reviewed book of Аleksander Maiorow is devoted to the problems of social-political relationships in Southern-Western Rus’ in the XІ – beginning of the XІІІ century. In the book special attention is paid to the process of foundation of urban communities, struggle for independence from Kyiv, particularities of political development, inter-community contradictions and conflicts.